Rewriting the Nation : British Theatre Today. - Sierz, Aleks (Plays and Playwrights., 2011)
In recent years British theatre has seen a renaissance in playwriting that has been accompanied by a proliferation of writing awards, new writing groups and a ceaseless quest for fresh, authentic voices that will ensure the vitality and relevance of theatre in the twenty-first century. Rewriting the Nation is a perfect companion to Britain''s burgeoning theatre writing scene that will prove invaluable to anyone wanting a better appreciation of why British theatre - at its best - remains one of the most celebrated and vigorous throughout the world. The books opens by defining what is meant by '